Enhancing Porters’ Rights in Mountain Tourism: Mount Semeru in Bromo Tengger Semeru National Park - Angling Galih Cahaya Widiyanto (Program Pascasarjana, 2020)
This study aims to investigate the implementation of rights focusing on the policy and working practices of porters. A total of nine respondents, including two National Park employees, two tour operator representatives, and five porters, participated in the interviews. Data from observation and interviews analyzed through a qualitative descriptive paradigm. Overall interviews revealed that Bromo Tengger Semeru National Park policies have not adequately covered issues on portering activities. Existing policies are limited to the tariff, guided trekking, and organizational aspects of the porters’ association. A high degree of effectiveness might be achieved through the involvement of related parties; however, that was not accessible. Some barriers in budgeting and communication appeared to determine that such policies are not yet effectively implemented. Involvement in policy making was indicated absent, since porters and stakeholders were not well facilitated. Monitoring and evaluation systems are carried alone by the National Park. In addition to that, the absence of policies on porters’ working conditions has been indicated to contribute to unfavorable working conditions of porters, including excessive workloads and uncertain weight limitations.Keywords: mountain tourism, Mount Semeru, porters.